2017
DOI: 10.1016/j.jtho.2016.11.2218
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1/1b Study Evaluating Trametinib Plus Docetaxel or Pemetrexed in Patients With Advanced Non–Small Cell Lung Cancer

Abstract: Trametinib-plus-chemotherapy combinations were tolerable. Clinical activity exceeding the ORRs previously reported with docetaxel or pemetrexed alone in KRAS-mutated NSCLC and meeting prespecified criteria was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Trametinib, has been evaluated in a phase I trial in combination with docetaxel or pemetrexed in advanced NSCLC patients with or without KRAS mutations [ 17 ]. Both combinations showed activity in KRAS mutant and wild-type tumors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trametinib, has been evaluated in a phase I trial in combination with docetaxel or pemetrexed in advanced NSCLC patients with or without KRAS mutations [ 17 ]. Both combinations showed activity in KRAS mutant and wild-type tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Different strategies evaluated an epigenetic approach, using cyclin-dependent kinases, heat shock proteins or focal adhesion inhibitors [ 12 14 ]. Several researchers wagered on inhibitors of downstream effectors of the KRAS signaling pathways (PI3K/AKT/mTOR and RAF/MEK/ERK) without significant success [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rash, diarrhea, and peripheral edema were the main adverse events, but those were manageable. A phase I/Ib study evaluating trametinib plus docetaxel or pemetrexed in patients with advanced KRAS-mutant non-small cell lung cancer (NSCLC) showed that the primary endpoint of overall response rate (ORR) was met for both combinations [ 30 ] (ClinicalTrials.gov number, NCT01192165).…”
Section: Mek Inhibitors Approved By the Us Food And Drug Administrmentioning
confidence: 99%
“… 43 Trametinib has also been tested in combination with chemotherapy, showing interesting outcomes in an exploratory subpopulation analysis of a phase I study in the subset of patients with G12C KRAS mutations (4 of 10 patients with confirmed response and 8 of 10 with disease control). 44 …”
Section: Targeting Kras In Nsclc Patientsmentioning
confidence: 99%